The Role of Health-Related Quality of Life in Early Discontinuation of Chemotherapy for Breast Cancer - Lisa C. Richardson; Wei Wang; Abraham G. Hartzema; Samuel Wagner (2007)
Abstract: To examine the role of health-related quality of life (HRQOL) in early treatment discontinuation among women enrolled in a breast cancer clinical trial. A total of 464 women were enrolled in the Eastern Cooperative Oncology Group randomized controlled trial of adjuvant regimens comparing six cycles of cytoxan, adriamycin and 5-flurouricil (5-FU) with a 16-week regimen (weekly therapy with cytoxan, adriamycin, vincristine, methotrexate, and 5-FU) among women with lymph node positive breast cancer. One hundred sixty-four women participated in the HrQL substudy using the Breast Chemotherapy Questionnaire, which was designed to measure HRQOL in women receiving chemotherapy. Changes in global HRQOL score were examined over time as a predictor of early treatment discontinuation using generalized estimation equations (GEE) modeling and Cox proportional hazards regression. We considered early treatment discontinuation as a longitudinal binary variable determined at each time point HRQOL was measured. The results of multivariate GEE model fitting indicated that declines in HRQOL (p = 0.04), older age (p = 0.02), higher degree of nausea (p = 0.02), higher degree of neurosensory toxicity (0.03) and lower degrees of hair loss (p = 0.004) were correlated with early treatment discontinuation. We then fitted a proportional hazard regression model for time to early discontinuation with HRQOL score as a time-dependent covariate. The results were identical. Declines in HRQOL during therapy predicted early treatment discontinuation even after accounting for age and chemotherapy-related side effects. In the age of ever more aggressive treatments for breast cancer, women's perception of the impact of these treatments on their lives will become more important.